Strategic Decision Analysis for Capacity Expansion with Migration for Semiconductor Assembly Industry - J Chen, Yenming (IJRDO - Journal of Applied Management Science, 2017)
This paper aims to understand strategic decision-making for capacity expansion via the use of the analytic network process, and to investigate further the difference in policies for capacity expansion in a situation of capacity migration. As the government’s westward policy slackens, and industries strive for business growth, higher profits competency, they have moved their products and capacity to China as they realize the larger labor population, lower production cost, easier land access and additional premium policies there, a phenomenon termed capacity migration. This study focuses on how semiconductor assembly industries make capacity expansion strategies while facing capacity migration. As most strategic analysis methods cannot provide actual manipulation methods, this research aims to build a multi-principle strategy model that can provide operable methods for abstract decisions. Findings of this study reveal that in the industrial environment where there is capacity migration, the semiconductor assembly industry should considers the Preemption Strategy when making capacity expansion strategic decisions.